The Efficacy and Safety of Hypofractionated Radiation Therapy With Tomotherapy for Advanced or Recurrent Hepatocellular Carcinoma - Shen, Jie; Yan, Jing; Zhu, Sihui; Kong, Weiwei; Zou, Zhengyun; Liu, Juan; Li, Shuangshuang; Liu, Baorui (Frontiers in Oncology, 2021)
The effects of radiotherapy on hepatocellular carcinoma (HCC) still remain to be further proved. The dose of radiotherapy is generally 2Gy*25f. In the current study, we prospectively investigated the clinical outcomes of advanced or recurrent HCC patients who received hypofractionated radiotherapy at a dose of 5Gy*10f with tomotherapy. A study involving hypofractionated radiotherapy (5Gy*10f) based on TOMO was conducted in HCC patients with Child-Pugh grade A or B who were unsuitable candidates for resection or radiofrequency ablation or with residual disease after transarterial chemoembolization (TACE). The prescription dose was 50 grays in 10 fractions. From Sep. 2016 and Dec. 2017, 65 patents were evaluated with a median follow-up of 24 months (range: 7–41 months). 10 patients were treatment-naïve (failure to undergo surgery or intervention due to the presence of a portal or portal branch tumor thrombus), 15 patients were treated for residual HCC after TACE as salvage therapy, and 40 cases were treated for recurrent HCC. The median overalls survival (OS) of these patients was 18 months. Among them, 27 patients classified as BCLC stage B had a median OS of 22 months. Moreover, 28 patients classified as BCLC stage C had a median OS of 14 months. None of the patients experienced recurrence in the area of radiotherapy. The local control rate of primary tumor at 3 months, 6 months, 1 year and 2 years was 100%. The 3-month survival rate was 100%, the 6-month survival rate was 100%, the 1-year survival rate was 75.4%, and the 2-year survival rate was 43%. In addition, 14 patients had the opportunity to continue the treatment of PD-1 antibody after the disease progression, and their prognosis was not surprisingly better compared with the patients who did not receive PD-1 antibody treatment (NR vs. 15 months, P=0.04). No serious side effect was found in all patients during and after radiotherapy. Hypofractionated radiotherapy (5Gy*10f) based on TOMO achieved high local control rate and OS with tolerable toxicities for HCC patients. TOMO therapy could be used to effectively against HCC in treatment-naive, intrahepatic failure, residual disease, and recurrent settings.